Real-time 3D temperature reconstruction in microwave cancer hyperthermia from scarce temperature measurements - Rossella Gaffoglio; Giorgio Giordanengo; Marco Righero; Marcello Zucchi; Maryam Firuzalizadeh; Giuseppe Musacchio Adorisio; Aurora Bellone; Alberto Vallan; Guido Perrone; Giuseppe Vecchi (Nature Communications)
Abstract Oncological microwave hyperthermia is a clinically proven sensitizer of radio- and chemo-therapies; it acts by selectively increasing the temperature of tumor cells by means of antenna applicators. Its current limitations mostly come from the inability to reliably predict, and hence control, temperature inside the patient during treatment, especially for deep-seated tumors. Simulations are employed in treatment planning, but due to related uncertainties invasive thermometry is necessary, usually via catheters. Being invasive, their use must be minimized and provides very limited spatial information. Here, we demonstrate an approach to obtain 3D temperature information in real time from few measurement points via massive use of high-performance simulations carried out prior to treatment. The proposed technique is tested both in a fully anthropomorphic in-silico scenario, and in an experimental controlled setting. The obtained results demonstrate the potential of the proposed method as a low-cost real-time temperature monitoring technique in cancer hyperthermia. Use with intra-luminal, minimally-invasive catheters is supported by the positive outcome experimentally obtained using data points directly acquired in the trachea-mimicking phantom structure.